DIGITAL ACCOUNTING SKILLS AND STRATEGIC PARTICIPATION DRIVING SUSTAINABLE CAREER SUCCESS - PHONGKRAPHAN, Nattharawee; NAMBURI, Nantharat (Thai Interdisciplinary and Sustainability Review, 2026)
This mixed-methods study investigates the causal mechanisms linking digital-era professional accounting skills to the sustainable career success of Thai accountants. Employing an Explanatory Sequential Design, quantitative data were gathered from 400 practitioners in Quality Accounting Firms and analyzed using Structural Equation Modeling (SEM). Subsequent qualitative data from 10 key informants were evaluated via content analysis. The empirical results demonstrate that digital and data analytics skills, personal attributes, strategic communication, and problem-solving capacities significantly, yet indirectly, influence career success. Crucially, this relationship is fully mediated by the practical application of these skills in the workplace and by accountants’ active participation in organizational decision-making. Qualitative insights further validate these findings, highlighting a vital paradigm shift from traditional technical roles to strategic business partnerships. Ultimately, the study proposes a comprehensive strategic framework designed for accounting firms to cultivate these multifaceted competencies. By integrating advanced technology use with ethical integrity and continuous learning, this framework ensures that Thai accountants can adapt effectively, create organizational value, and achieve long-term professional success in the rapidly evolving digital economy.